Estudos de pré-formulação e formulação de Vismia guianensis (Aubl.) Choisy - CAMELO, Sarah Regina Pereira (Universidade Federal do Pará, 2014)
The obtention and evaluation of a new herbal formulation from Vismia guianensis (Aubl.) Choisy was determined by parameters of quality control. Physical-chemical characterization in plant raw material dried and crushed, its extract of the tincture and semi-solid formulation with antimicrobial activity. For the characterizations specific parameters for herbal drugs contained in the Brazilian Pharmacopoeia 4th Ed were used, the thermal analysis: thermogravimetry, differential thermal analysis and differential scanning calorimetry and infrared and ultraviolet spectroscopy. The evaluation of the antimicrobial activity by the disk diffusion method in solid identified the sensitivity of S. aureus (ATCC 25923) to the dried extract dissolved in DMSO at concentrations of 500, 250, 125 and 62.5 mg / mL. The HPLC drawing the profile of the composition of the sub-fractions A and B from the ethyl acetate fraction of the tincture and showed the range of maximum absorption at 290 nm similar to the maximum capacity of emodin being used a reference standard and an external marker. The method validation was performed by ultraviolet spectrophotometry, demonstrating a selective method, linear, repeatable and robust. Thermal analysis showed possible incompatibilities between the binary mixture of the extract of the tinsture with hydroxyethylcellulose and propylene, then obtaining non-homogeneous gel due to precipitation of proteins, triggered by the polyphenol-protein interaction. A preliminary evaluation of the stability of the formulation obtained remained within the normal parameters, show results within acceptable limits for the centrifuge tests, thermal stress and organoleptic characteristics.